Studying the Magnetohydrodynamics for Williamson Fluid with Varying Temperature and Concentration in an Inclined Channel with Variable Viscosity (Baghdad Science Journal, 2021)
In this paper, the Magnetohydrodynamic (MHD) for Williamson fluid with varying temperature and concentration in an inclined channel with variable viscosity has been examined. The perturbation technique in terms of the Weissenberg number  to obtain explicit forms for the velocity field has been used. All the solutions of physical parameters of the Darcy parameter , Reynolds number , Peclet number  and Magnetic parameter  are discussed under the different values as shown in plots.